When Attitudes Become Obstacles: An Exploratory Study of Future Physicians' Concerns about Reporting Child Maltreatment - Morgan E. Dynes; Stephne S. Rasiah; Michele Knox (MDPI AG, 2023)
Background: Child maltreatment (CM) makes up a significant portion of events under the larger umbrella term of adverse childhood experiences (ACEs). Therefore, we need to develop a competent healthcare workforce that is prepared to assess and report CM in order to create a comprehensive framework for assessing and addressing ACEs. The objective of the present study was to examine the obstacles to reporting CM among a sample of future physicians. Methods: Two samples of medical students and residents (N = 196) completed the Healthcare Provider Attitudes Toward Child Maltreatment Reporting Scale and rated how likely they would be to report suspected CM. Results: Medical students were found to have more negative feelings about and perceive more obstacles to reporting CM compared to residents in our sample. Scores on the Reporting Responsibilities subscale were not significantly associated with increased likelihood of reporting CM. However, lower scores on the Concerns about Reporting subscale were related to an increased likelihood of reporting CM. Conclusions: Future physicians who perceived fewer obstacles to reporting CM reported being more likely to report suspected CM. Misinformed fears about outcomes such as retaliation, removal of the child from the home, and being sued may interfere with future physicians' adherence to mandated reporting responsibilities. Efforts should be made early in physician education to identify and address common myths and misconceptions around mandated reporting and its outcomes.